Effect of endurance training on performance and muscle reoxygenation rate during repeated-sprint running - Buccheit, M.; Ufland, P. (European Journal of Applied Physiology, 2011)
The aim of the present study was to examine the effect of an 8-week endurance training program on repeated-sprint (RS) performance and post-sprints muscle reoxygenation rate in 18 moderately trained males (34 ± 5 years). Maximal aerobic speed (MAS), 10 km running and RS (2 × 15-s shuttle-sprints, interspersed with 15 s of passive recovery) performance were assessed before and after the training intervention. Total distance covered (TD) and the percentage of distance decrement (%Dec) were calculated for RS. Between-sprints muscle reoxygenation rate (Reoxy rate) was assessed with near-infrared spectroscopy during RS before and after training. After training, MAS (+9.8 ± 5.8%, with 100% chances to observe a substantial improvement), 10 km time (-6.2 ± 5.3%, 99%), TD (+9.6 ± 7.7%, 98%), %Dec (-25.6 ± 73.6%, 93%) and Reoxy rate (+152.4 ± 308.1%, 95%) were improved. The improvement of Reoxy rate was largely correlated with improvements in MAS [r = 0.63 (90% CL, 0.31;-0.82)] and %Dec [r = -0.52 (-0.15;-0.76)]. Present findings confirm the beneficial effect of endurance training on post-sprint muscle reoxygenation rate, which is likely to participate in the improvement of repeated-sprint ability after training. These data also confirm the importance of aerobic conditioning in sports, where repeating high-intensity/maximal efforts within a short time-period are required.